LONG COVID-19 AND QUALITY OF LIFE : A SYSTEMATIC REVIEW - Frida Setiawan, Yenny (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The majority of patients receiving Covid-19 report experiencing effects ranging from mild to severe. Ten percent to fifteen percent of patients develop severe symptoms, and five percent of cases progress to a critical stage. In many patients, particular symptoms may persist for several weeks or months after recovery has taken place. Also a possibility in more benign circumstances. During this stage of the process, the patient is no longer infectious. Patients experienced a wide range of different outcomes after Covid-19. Long covid syndrome is characterized by the persistence of clinical symptoms in Covid-19 patients for 4 to 12 weeks after the initial onset, or for 12 weeks or more, which is known as chronic post-covid syndrome, according to the World Health Organization (WHO) in the year 2020. Long- Covid syndrome is also known as post-covid syndrome. This drawn-out process of covid production results in symptoms such as fatigue, headache, shortness of breath, anosmia, muscle weakness, and cognitive impairment. Patients who have long- Covid suffer from a multitude of difficulties, including those related to the heart, the respiratory system, cognitive function, and so on. After pulmonary disorders, cognitive disorders are the most frequent type of illness. Patients diagnosed with both conditions frequently report having a lower quality of life due to the effects of long-Covid.